The interaction between ferroptosis and myocardial ischemia–reperfusion injury: molecular mechanisms and potential therapeutic targets - Tiantian Zhang; Yue Han; Yongcheng Wang; Xiaoyu Wang; Mingchen Zhao; Ziyang Cheng; Shiliang Zhang (European Journal of Medical Research)
Abstract Myocardial ischemia–reperfusion injury (MIRI) is a common fatal event in cardiovascular diseases. Oxidative stress, energy metabolism disorders, and inflammatory responses that occur during this process cause severe damage to myocardial cells. Ferroptosis is a novel form of cell death closely related to cellular damage in MIRI. Numerous studies have demonstrated that specific active ingredients can regulate iron homeostasis and inhibit ferroptosis, thereby protecting myocardial function and enhancing the prognosis of patients. At the same time, traditional Chinese medicine monomers also provide a new perspective for the treatment of MIRI. This review summarizes the recent advances in understanding the mechanisms underlying ferroptosis, with the aim of providing potential novel therapeutic strategies for the clinical management of MIRI.